Estrategias lúdicas y desarrollo de habilidades sociales para niños de inicial 2 de la Escuela Dr. “Reinaldo Espinoza Aguilar” 2023-2024 - Granda López, Jessica Viviana (2024)
The education of children is crucial throughout the world, but it faces various challenges, particularly in formal and early childhood education. UNESCO has identified a lack of appropriate social skills and inadequate management of social relationships among children in schools. This is reflected in alarming figures: 22.9% of children suffer from aggression, and 25.8% experience bullying. Utilizing playful strategies and developing social skills is important because these are fun ways to teach younger children about teamwork and interaction, not only with their peers but also with the community. The present research aims to identify teachers' perceptions of playful strategies in the social development of children, as well as describe activities that can help young children and assess the importance of these activities at Dr. Reinaldo Espinoza Aguilar School. The methodology used in this project was a qualitative, non-experimental research method, beginning with observation to identify the problem, recognize the variables, interview the teacher, and offer an observation guide for children. Based on the results, I can conclude that teachers are aware of play strategies and use some of them, but observation revealed that teachers do not apply these strategies correctly, especially in the development of social skills, as children do not work in groups and have very little communication with each other. Keywords: game-activities-methodology-community